Manajemen Pengelolaan Perpustakaan Sekolah di SDN 3 Sikur Tahun Pelajaran 2017/2018 - Saputra, Ahmad Fauzi Ardian; Musaddat, Syaiful; Zain, Moh. Irawan; Marijo, Okta D. S. F. (Pendagogia: Jurnal Pendidikan Dasar, 2022)
This study aims to describe the school library management at SDN 3 Sikur which includes aspects of 1) planning 2) organizing 3) implementation 4) supervision in the library and 5) service. This research is a qualitative research using a case study approach. Sampling using purposive sampling technique. The research subjects were principals, librarians, teachers and students. The place of research is the library of SDN 3 Sikur, East Lombok Regency. Data collection methods are interviews, observation, and documentation. Data were analyzed using the Interactive Model Miles and Huberman with the stages of data reduction, presentation and conclusion. The validity of the research data is a credibility test by triangulation of techniques and sources. The results showed that library management at SDN 3 Sikur includes: 1) Library planning at SDN 3 Sikur consists of students, costs, personnel, and infrastructure. Library planning is supported by existing resources and adjusted to the needs of students determined through a joint meeting with all parties at SDN 3 Sikur. 2) Library organization at SDN 3 Sikur is good; 3) The implementation of library management at SDN 3 Sikur went well; 4) Supervision carried out by the principal is quite good; and 5) The services provided by SDN 3 Sikur use a reference circulation service using a mixed service system (open and closed).